The Methodological Foundations of the Process of Transformation of Industrial Enterprises - Mirzaev Otabek Davronovich (Zien Journals, 2022)
This article discusses the implementation of the transformation process in industrial enterprises, the mechanism of transformation and the tasks of the enterprise in terms of transformation processes.
Keywords: industry; enterprise; mechanism; transformation processes